Drain closure: method and safety aspects / Ahmad Syahid Adnan - Adnan, Ahmad Syahid (Universiti Teknologi MARA, Perak, 2013)
This report briefly describes the method and safety aspects in drain closure construction using concrete truck (ready-mix concrete method), and is the result based on the experience of 5 months of practical training placed at the construction site located at Kg. Telaga Daing, Kuala Terengganu. This report varies into sections and starts with the company background and the background of the construction project. The project shows that the method and safety aspects of drain closure construction is not as easy as the title stated. This is due to the many parties involved in this project. In this report, a detailed explanation about the construction method of drain closure with explained safety aspects during the construction. During the process of construction, some problems were identified, and this report also explained the solutions to overcome the problems. As a conclusion, this report contains detailed explanation of the method and safety aspects of constructing drain closure, practically to readers.